Influence of hydrothermal exposure on surface characteristics and corrosion behaviors of anodized titanium. (21st February 2014) - Chen, Zhaoxiang; Zhou, Kun; Lu, Xuehong; Lam, Yee Cheong
<x xml:space="preserve">Abstract</x> Titanium surface was modified by anodization in phosphoric acid solution at the voltages of 100 and 250 V, respectively. Surface characteristics and corrosion behaviors of anodized titanium were investigated before and after hydrothermal exposure in 3.5 wt.% NaCl solution at 160 °C for 24 h. It was found that anodization at 100 and 250 V resulted in the formation of a dense and a porous TiO2 layer, respectively. The existence of anatase in the oxide layers of the 250‐V samples was confirmed by X‐ray diffraction analysis but not in the oxide layers of the 100‐V samples. After the hydrothermal exposure, the surface morphology of the 100‐V sample changed significantly, and discrete nanorods were formed on the surface. In contrast, the 250‐V sample basically preserved their original surface structures after the exposure except that numerous closely packed nanoparticles emerged on the surface. X‐ray diffraction analysis indicated that the exposure transformed the amorphous oxides into crystalline anatase. The corrosion behavior investigation of anodized titanium showed that the hydrothermal exposure had slight influence on the corrosion resistance of the 100‐V samples but decreased the corrosion resistance of the 250‐V samples significantly. Copyright © 2014 John Wiley & Sons, Ltd.